Evaluating the inclusion of tympanometry in population-based surveys of hearing loss. Issue 9 (24th September 2022) - Bright, T; Youngs, R; Faal, Y; Hydara, A; Yip, J L Y; Mactaggart, I; Polack, S
Abstract: Objective: This study aimed to determine the implications of including tympanometry in the Rapid Assessment of Hearing Loss survey protocol. A comparative study design was employed, with findings from otoscopy compared with the results of tympanometry. Method: A population-based survey of the prevalence and causes of hearing loss among adults aged over 35 years in The Gambia was conducted. Clinical assessments included air conduction audiometry, otoscopy and clinical history. Otoscopy outcome was recorded and for those with hearing loss, a probable cause was assigned. Following otoscopy, tympanometry was completed. Otoscopy outcome was not changed as a result of tympanometry. Clinician assigned cause was compared to the results of tympanometry. The proportion of causes potentially misclassified by excluding tympanometry was determined. Results: Among people with hearing loss, including tympanometry led to a higher proportion diagnosed with middle-ear conditions. Conclusion: The value of adding tympanometry to population-based survey protocols is a higher estimated proportion of hearing loss being attributed to middle-ear disease rather than sensorineural causes. This can inform service needs as more people will be classified as needing medical or surgical services, and a slightly lower number will need rehabilitative services, such as hearing assistive devices. It is highly recommended that tympanometry is included in the protocol.